2010
DOI: 10.1109/tnsre.2009.2023296
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Among Joint Motions Allows Classification of Parkinsonian Versus Normal 3-D Reaching

Abstract: In this paper, an objective assessment for determining whether a person has Parkinson disease is proposed. This is achieved by analyzing the correlation between joint movements, since Parkinsonian patients often have trouble coordinating different joints in a movement. Thus, the auto-correlation coefficient of single joint movements and the cross-correlation between movements in a pair of joints (hand, wrist, elbow and shoulder) were studied. These features were used to train and provide classification of subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Note that the accuracy is calculated as average accuracy of ten repetitions using ten-fold cross validation (average and standard deviation) of PD. The majority of these studies applied SVM classifiers to behavioral data of gait analysis [29], fine motor force tracking [30], analysis of wearable accelerometer sensors [31] or joint movement [32], and even voice recording [33]. The only previous SVM application to MRI data in the domain of PD analysed VBM pre-processed grey matter in 21 PD, 11 MSA-P and 10 PSP, and 22 healthy controls [34].…”
Section: Individual-level Svm Classification Analysismentioning
confidence: 99%
“…Note that the accuracy is calculated as average accuracy of ten repetitions using ten-fold cross validation (average and standard deviation) of PD. The majority of these studies applied SVM classifiers to behavioral data of gait analysis [29], fine motor force tracking [30], analysis of wearable accelerometer sensors [31] or joint movement [32], and even voice recording [33]. The only previous SVM application to MRI data in the domain of PD analysed VBM pre-processed grey matter in 21 PD, 11 MSA-P and 10 PSP, and 22 healthy controls [34].…”
Section: Individual-level Svm Classification Analysismentioning
confidence: 99%
“…The frequency distribution of the kinematics data determines the types of statistical analyses that can be validly carried out on the data (Limpert et al, 2001; Limpert and Stahel, 2011). The PD literature often uses ANOVA (analyses of variance) and regression analyses to test a hypothesis see for example (Poizner et al, 1998; Messier et al, 2007; Chan et al, 2010; Mera et al, 2011; Sande De Souza et al, 2011; Venkatakrishnan et al, 2011) just to cite a few. However, these methods require that the data be normally distributed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Pohl et al used the cross-correlation technique to examine the joint couplings between rearfoot and four adjacent joint variables during [ ( F i g . _ 1 ) T D $ F I G ] walking, and Chan et al showed that cross-correlation of upper extremity joint movements could be used for classification between normal and Parkinsonian individuals when reaching for a target [22,23]. In contrast with these past studies, in the present effort, we seek to characterize joint couplings throughout the entire locomotive apparatus using a single representative diagram.…”
Section: Introductionmentioning
confidence: 99%
“…For example, cross-correlation has been used to identify the synchronization of motor unit firings or to perform pattern recognition of EMG signals [14,18]. Cross-correlation between body movements has also been used [22,23]. For example, Pohl et al used the cross-correlation technique to examine the joint couplings between rearfoot and four adjacent joint variables during [ ( F i g .…”
Section: Introductionmentioning
confidence: 99%